PENGARUH KOMPOSISI SORBITOL DAN PATIBERAS SEBAGAI EDIBLE COATING TERHADAP MUTU BUAH SALAK ( Salaca zalacca ) SELAMA PENYIMPANAN - Sumatera Tarigan; Hamonangan Catur Damanik (Universitas Quality, 2018)
The research was conducted with the aim to determine the right concentration between rice starch and sorbitol, and to determine the effect of the storage time of salacca fruit given an edible coating. The research used factorial RAL (complete randomized design) method. Factor 1 = Sorbitol concentration, cassava starch and distilled water consists of: S0 = Sorbitol concentration 0 ml (control); S1 = Sorbitol concentration of 1 ml + pb 10 g + aquades = 500 ml; S2 = Concentration of sorbitol 3 ml + pb 10 g + aquades 500 ml; S3 = The concentration of 5 ml sorbitol + pb 10 g + 500 ml distilled water; S4 = 7 ml sorbitol + pb 10 g + 500 ml distilled water; Factor 2 = Storage duration by consisting of: T0 = 0 days; T1 = 3 days; T2 = 6 days; T3 = 9 days; T4 = 12 days; T5 = 15 days. The results of the study were the influence of the use of sorbitol and rice starch as edible coatings on the durability of salak fruit by the use of sorbitol and rice starch on days 1-6 days.